Postgraduate Programme in Latin American Integration at The University of São Paulo (PROLAM): History, Development and Prospects - Cacciamali, Maria Cristina (2024)
The Graduate Programme in Latin American Integration at the University of São Paulo (PROLAM-USP) began its activities in 1988 focusing on regional integration. Its research, knowledge production, scientific dissemination, and community outreach activities are characterized by interdisciplinarity and comparative research methodology. In its history, the Programme has produced more than 500 theses and dissertations on Latin America. Its Lines of Research are Society, State, Economy and Environment; Communication, Literature, and Culture; and Political Practices and International Relations.